2014
DOI: 10.1007/s00792-014-0685-2
|View full text |Cite
|
Sign up to set email alerts
|

Picophytoplankton predominance in hypersaline lakes (Transylvanian Basin, Romania)

Abstract: The occurrence and importance of photoautotrophic picoplankton (PPP, cells with a diameter <2 μm) was studied along a trophic and salinity gradient in hypersaline lakes of the Transylvanian Basin (Romania). The studied lakes were found to be rich in PPP, with abundances (maximum: 7.6 x 10 6 cells mL -1 ) higher than in freshwater and marine environments of similar trophic conditions. The contribution of PPP to the total phytoplankton biovolume did not decrease with increasing trophic state as it was generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…1B, Table 2). Former studies (Schapira et al 2010;Somogyi et al 2014) reported that eukaryotic algae are the dominant in the picophytoplankton of saline environments between salinities 5 and 13%, which corresponded well with our observations.…”
Section: Sulphuric Bubbling Pools [Timsós (Apor) Baths]supporting
confidence: 82%
See 1 more Smart Citation
“…1B, Table 2). Former studies (Schapira et al 2010;Somogyi et al 2014) reported that eukaryotic algae are the dominant in the picophytoplankton of saline environments between salinities 5 and 13%, which corresponded well with our observations.…”
Section: Sulphuric Bubbling Pools [Timsós (Apor) Baths]supporting
confidence: 82%
“…However, it has been proven that natural aquatic habitats may harbour abundant planktonic communities in the coldest period of the year (Philips and Fawley 2002; Somogyi et al 2014), surprisingly even blooms of planktonic phototrophs could emerge (Álvarez et al 2009;Pálffy et al 2014;Somogyi et al 2009;Üveges et al 2012). Since microorganisms of inland waters have a great impact on biogeochemical cycles, may effect water quality and interact with other aquatic organisms, describing the taxonomy and ecology of microbes present in winter is crucial to understand their role in the ecosystem (Bertilsson et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with Ursu Lake, the photic zone of Fara Fund Lake hosts smaller communities of phototrophic microorganisms as shown by the low chlorophyll a content reported in this study (see Table 1) and by previous works (Keresztes et al, 2012). Thanks to our microscopy and molecular analyses (doi: 10.5061/dryad.2gm06), we consider that oxygen levels in the euphotic zone of Fara Fund Lake were mostly generated by the photosynthetic activity of Dunaliella algae (see also Somogyi et al, 2014). Microbial communities capable of organic carbon degradation were found to be distributed along the water column of the lake, spreading from the oxic (Halobacteriales and Nanohaloarchaeota) to the suboxic layers (Halanaerobacter, Halanaerobium and Halorhabdus) (Supplementary Table S6).…”
Section: Community Physiology Inferences In Ursu and Fara Fund Lakessupporting
confidence: 71%
“…Other studies have come to similar conclusion, winter phytoplankton primary production has 613 been found to primarily depend on light rather than on nutrient availability in various water 614 bodies, such as an alkaline pan (Pálffy et al, 2014) and a humic, boreal lake (Tulonen et al, 615 1994). Grazing might also be a determining factor, but in winter zooplankton activity is 616 greatly limited.…”
mentioning
confidence: 49%